The Pedogenesis of Inceptisols on Southeast Toposequence of Mount Manglayang in West Java, Indonesia - Ganjar Herdiansyah; Mahfud Arifin; Abraham Suriadikusumah (Geological Agency, 2022)
DOI:10.17014/ijog.9.2.195-208The most potential soil order in Indonesia is dominated by Inceptisols, whereas the topography combined with a climatic factor are the main factors to regulate pedogenetic process. This research was intended to determine the pedogenetic process and soil development on various terrain positions at the southeast toposequence of Mount Manglayang areas that have hilly topography. The researched area was 28.83 ha. Based on those conditions, this research aims to study the pedogenetic process and soil development in the southeast slope toposequence of Mount Manglayang, the relationship between the physical, chemical, and mineralogical soil properties, the soil classification to family level based on soil taxonomy, National Soil Classification, and FAO soil classification systems. This research used survey, descriptive, and comparative methods. The result showed that the pedogenetic processes identified were the formation of B horizon through clay accumulation, soil colour, and soil structure development, and the formation of amorphous kaolinite and halloysite minerals. Based on soil taxonomy, the soil were classified as Fluventic Humudepts, coarse-loamy, kaolinitic, isohyperthermic at the upper slope and Fluventic Dystrudepts, fineloamy, kaolinitic, isohyperthermic at the middle and lower slopes. According to National Soil Classification, the soil is Humic Cambisol at the upper slope, Distric Cambisol at the middle slope, and Cromic Cambisol at the lower slope. FAO classified the soil as Umbric Cambisols at the upper slope and Dystric Cambisols at the middle and lower slopes.